Age of Withdrawal from the Labour Force in OECD Countries - Scherer, Peter (OECD Publishing, 2002)
The age of withdrawal from the labour force is an issue of great policy importance. As populations age, an accurate understanding of trends and cross-country differences has become important. However, the age of withdrawal from the labour force cannot be measured directly using cross-sectional data only. Direct observation of net withdrawal rates are needed. This paper presents estimates of these rates derived from comparisons of activity rates at five year periods. A method is proposed (in the Annex) for using data on the stock of people employed at age 65 and above to derive estimates of the net rate of withdrawal at ages 65 and above. The results indicate that net age of withdrawal for men and for women is similar in most countries, and that both show strong cyclical fluctuations ...
Keywords: Social Issues/Migration/Health